KARAKTERISTIK PETERNAK YANG BERGABUNG DI BADAN USAHA MILIK DESA UNIT PETERNAKAN SAPI POTONG - Rohani, ST; Hastang, Hastang; Diansari, Pipi; Darwis, Muhammad; Kurniawan, Muhammad Erik; Astaman, Putra; Hikmah, Aulia Nurul; Basri, Zulkifli (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2023)
The phenomenon of national beef supply is still a very interesting polemic to be studied in the world of research. The purpose of this study is to describe the characteristics of farmers who join the BUMDes beef cattle unit. This research was conducted in Bantaeng Regency. The type of research used descriptive research research. The research sample was 30 farmers who were members of the BUMDES beef cattle farming unit which was done by simple randomization. Data were collected through interviews and analyzed using descriptive statistics. The results showed that the characteristics that influenced farmers who joined the BUMDes were based on age, gender, education level, family dependents, farming experience, and number of livestock ownership. The research conclusion is that the characteristics of farmers who join the BUMDES beef cattle farming unit in Bantaeng Regency are at productive age and male, relatively low education level, the number of family dependents of farmers 1-3 people, farming experience between 1 to 3 years with livestock ownership scale ranging from 1-4 beef cattle